Associations among employment and industries of Slovak economy - Gabriela Kolvekova; Gabriela Kolvekova (Institute of Economic Research (IER), 2017)
Urban areas are as important as rural ones for regional development. This paper observes especially the position of cities, urban areas in the context of global value chains - GVC. Global value chains reflect specialization and labour division of companies, mostly multinational enterprises - MNEs. MNEs can be considered for flagships of some industries. Such flagship influence suppliers and purchasers. MNEs are a part of networks or do have got an access to such networks that combine dispersion of the value chain the boundaries of the firm and across national borders and. The impetus of this humble work was to look at position of Slovak cities (Bratislava, Žilina) in order to look for sectors that can help to develop the city and its adjacent regions, particularly cross-border regions. The paper discussed how the attribute of the cross-border regions gives the cities more advantageous position in GVC. Applying method of location quotient allowed to shed a light on GVC, which cities participate in. Some cities were in a position to take advantage of participation in GVC. Examined cities are located in the western part of Slovak Republic. Discussion about the attribute of the cross-border regions can stimulate new ideas for finding causalities in city sprawl or in specialization patterns in industrial structure of the city. Discussion further fosters the comparison of two cities strengths and weakness of each of them that were summarized in terms of employment and industrial exploitation of GVC. It is the first finding and value added of the paper. Second one, method of location quotient is simple, but provides clear evidence on the regional development or decline in particular industries and time of observation.
Keywords: J21; Q01; R12; 330; employment; value chains; industry